Therapeutics and management of persistent cases of Canine Transmissible Venereal Tumour: an Update - Biswas, Newton; Singh, Kiran; Sharma, Sushil; Parmar, Sunil; Srivastava, Neeraj; Khan, MH (Animal Reproduction Update, 2024)
Canine Transmissible Venereal Tumour (CTVT) is a contagious venereal tumour in dogs. It is mostly transmitted through sexual contact but can also spread through sniffing, licking, biting, and scratching the affected area. It is a contagious tumour, mostly prevalent in mongrels, in dogs exhibiting high levels of sexual activity coupled with roaming behaviour in tropical and subtropical climates. Recently, the incidence of TVT has been found to be increasing, especially in urban areas, where pet parents often come across their animals showing oozing of serosanguinous fluid from anomalous tumorous growth in external genitalia. This frequently turns out to be TVT. Cytological and histopathological findings are used to make a definitive diagnosis. Treatment options may include chemotherapy, surgery, radiotherapy, and immunotherapy, with chemotherapy often being the preferred choice. In recent times pet owners have reported recurrence of the case confirmed earlier as TVT. This has further implication of development of toxicity due to repeated use of chemotherapy. This necessitates an urgency to review the current therapeutic approaches and reformulate them with effective alternative regimens. Lately, several new therapeutic protocols have been developed for TVT, which are very promising, especially for the cases that have shown resistance and recurrence to certain treatments. It is imperative that treating veterinarian besides being thorough about therapeutic knowledge, especially dosage calculation (Body weight vs body surface area) should also get acquainted with preventive and control measures. This particular paper captures the manifold developments in different areas dealing with therapeutic alternatives, prevention, and control of TVT.
Keywords: Sticker’s sarcoma, Diagnosis, Treatment, Vincristine, Lomustine